Microfluidics systems with societal impact in Analytical Methods. Issue 41 (15th October 2018) - Roper, Michael G.; Easley, Christopher J.; Regan, Fiona; Southall, Maria E.
Abstract : Guest Editors Michael Roper, Christopher Easley and Fiona Regan, alongside Deputy Editor Maria Southall, introduce the Analytical Methods themed collection on microfluidic systems.